Education and intergenerational social mobility in the US and four European countries - Breen, R (Oxford University Press, 2019)
I draw on the findings of a recently completed comparative research project to address the question: how did intergenerational social mobility change over cohorts of men and women born in the first two-thirds of the twentieth century, and what role, if any, did education play in this? The countries studied are the US, France, Germany, the Netherlands, and Sweden. Notwithstanding the differences between them, by and large they present the same picture. Rates of upward mobility increased among cohorts born in the second quarter of the century and then declined among those born later. Among earlier born cohorts, social fluidity increased (that is, the association between the class a person was born into and the class he or she came to occupy as an adult declined) and then remained unchanged for those born after mid-century. The association between class origins and educational attainment followed much the same trend as social fluidity. This suggests that growing equalization in education may have contributed to the increase in social fluidity. In our analyses we find that this is so, but educational expansion also led to greater fluidity in some countries. There is also a strong link between upward mobility and social fluidity. Upward mobility was mostly driven by the expansion of higher-level white-collar jobs, especially in the 30 years after the end of the Second World War. This facilitated social fluidity because people from working class and farming origins could move into the service or salariat classes without reducing the rate at which children born into those classes could remain there. Educational expansion, educational equalization, and rapid structural change in the economies of the US and Europe all contributed to greater social fluidity among people born in the second quarter of the twentieth century. For people born after mid-century, rates of downward mobility have increased: however, despite the lack of further educational equalization and less pronounced structural change, social fluidity has remained unchanged.